Reform of Criminal Procedure Law in Dealing with Transnational Cyber Crime - Henny Saida Flora; Kailie Maharjan; Elladdadi Mark; Jimmy Rian Fernando; Idrus Alghiffary (Rechtsnormen: Journal of Law, 2024)
Background: The rapid advancement of technology has led to a significant increase in transnational cybercrime, posing serious challenges to existing criminal procedure laws. Traditional legal frameworks often fall short in addressing the complexities and borderless nature of cybercrimes, necessitating comprehensive reforms to enhance international cooperation and effective law enforcement. Objective: This research aims to analyze the current inadequacies in criminal procedure laws regarding transnational cybercrime and propose necessary reforms to strengthen legal frameworks, ensuring efficient cross-border cybercrime management. Methodology: This study employs a qualitative research method, including a comprehensive literature review, analysis of existing legal frameworks, and expert interviews. The comparative analysis of different countries' approaches to cybercrime legislation provides insights into best practices and potential improvements. Results: The research findings reveal significant gaps in the current legal procedures, such as jurisdictional challenges, lack of standardized definitions, and inadequate international cooperation mechanisms. The study identifies key areas for reform, including harmonization of cybercrime laws, enhancement of mutual legal assistance treaties, and adoption of advanced technological tools for investigation. Conclusion: The reform of criminal procedure laws is imperative to effectively address transnational cybercrime. The proposed reforms emphasize the need for a unified legal framework, improved international collaboration, and utilization of modern technologies to ensure robust and adaptive legal responses to the evolving nature of cyber threats.